(untitled) (Research, Society and Development, 2021)
In the multinational company in question it was realized that the quality and productivity indicators were not being achieved. The present work has as purpose the application of the PDCA tool in the assembly lines of the company under study to reach the goals related to the productivity and quality indicators. The methodology applied to achieve the goals was developed based on bibliographical research, checking the current situation of the whole process and where the entire survey of the main problems and their causes was carried out. About to the factors that cause non-conformities in the indicators it was necessary to create a systematic for the development of activities involving various departments to improve communication and a frequency of daily checking of the progress of each project. As a result of the implementation of the systematic and mainly the use of the PDCA tool, there was a reduction in quality losses of approximately 0.01% and an increase in productivity of 0.16% in the first six months.